Assessing the accuracy of human-inspired electronic skin: A systematic review - Fahad AlShaibani; Vicente Grau; Jeroen Bergmann (Biosensors and Bioelectronics: X)
Electronic skin (e-skin) systems are devices that mimic the different sensing modalities of skin. While the modalities sensed can vary from temperature to tactile, the main inspiration for much of the research being conducted is mimicking the sensing modalities of human skin. Much research has been conducted on tactile sensing through e-skin, as interest grows in the use of e-skin with smart prosthetics and Virtual and Augmented Reality (VR/AR) applications. Being able to mimic the sophisticated ability for human hands to complete complex tasks of dexterity, using an e-skin as essential input system, is the goal of many research groups. In this systematic review, we provide a full overview on e-skin systems that focus on developing tactile sensing. The objective is to assess how accurately these systems mimic human skin tactile sensing modalities and how accurately the detected stimuli are sensed. The outcomes of the review show where the focus of the community is with regards to which modalities are being developed. Furthermore, information extracted from the papers that detail their quantitative accuracy in sensing these modalities is provided. With a total of 205 systems included insights on trends and a quantitative comparison of current e-skin systems are discussed. The limitations of the current methods applied and how they could be overcome are explored, in addition to highlighting the need for standardized experimental protocols to ensure e-skin systems can be assessed and compared more easily.